2017
DOI: 10.1016/j.bbr.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing GABA function within the medial prefrontal cortex or basolateral amygdala decreases sociability

Abstract: Introduction Decreased sociability is a symptom of psychiatric conditions including autism-spectrum disorder and schizophrenia. Both of these conditions are associated with decreases in GABA function, particularly in the medial prefrontal cortex (PFC) and the basolateral amygdala (BLA); structures that are components of the social brain. Here, we determined if decreasing GABA transmission within either the PFC or the BLA decreases social behavior. Methods Rats were implanted with cannulae aimed at either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 57 publications
4
35
1
Order By: Relevance
“…During early embroyonic development, GABAergic interneurons are involved with regulating cell migration, differentiation, and synapse formation (112). Rodent models suggest that decreasing GABA transmission in the mPFC decreases sociability (113), consistent with our view that E/I imbalance in the DMN can contribute to impaired social function in autism.…”
Section: Neurophysiological Basis Of Dmn Dysfunction In Asdsupporting
confidence: 86%
“…During early embroyonic development, GABAergic interneurons are involved with regulating cell migration, differentiation, and synapse formation (112). Rodent models suggest that decreasing GABA transmission in the mPFC decreases sociability (113), consistent with our view that E/I imbalance in the DMN can contribute to impaired social function in autism.…”
Section: Neurophysiological Basis Of Dmn Dysfunction In Asdsupporting
confidence: 86%
“…It is also recently reported that decreased GABAergic functions induce the sociability [ 14 ], which may be involved in the changes of our results concerning social interaction and preference (Fig. 4e-f ), as models of human autism-spectrum and schizophrenia [ 15 17 ].…”
Section: Discussionsupporting
confidence: 59%
“…Mice were evaluated for the effects of Trim67 deficiency on social preference using a 3-chamber choice test. This behavior has been associated with the hippocampus and parts of the amygdala ( Felix-Ortiz and Tye, 2014 ; Paine et al, 2017 ), both of which were decreased in size in Trim67 −/− brains. In the initial habituation phase, both Trim67 +/+ and Trim67 −/− mice made similar numbers of entries into each side chamber ( Trim67 +/+ ; 10.3 ± 1 right, 9.3 ± 0.7 left: Trim67 −/− ; 8.5 ± 0.9 right, 8.3 ± 0.8 left).…”
Section: Resultsmentioning
confidence: 98%